(2a-3b)(-2a+3b)-(3a-2b)(-3a-2b)
来源:学生作业帮助网 编辑:作业帮 时间:2024/11/30 02:03:35
xJ@_ He٤h0ɋ/PzR=HE<zn%2v1lv&B^gh Ш EЮgaRqS7ͥ>v|+ v3h4*7
U:d,.II4xUE8T8k-0%'2u9)V?2j7~l^@ص^
"i0ߵyZۗkƙ-~>&qn!c,V06L4пbIH!Tqsfd*N#Um)~r
(2a-3b)(-2a+3b)-(3a-2b)(-3a-2b)
(2a-3b)(-2a+3b)-(3a-2b)(-3a-2b)
(2a-3b)(-2a+3b)-(3a-2b)(-3a-2b)
(2a-3b)(-2a+3b)-(3a-2b)(-3a-2b)
= -(2a-3b)²+(3a-2b)(3a+2b)
= -(4a²+12ab+9b²)+9a²-4b²
=5a²-12ab-13b².
(2a-3b)(-2a+3b)-(3a-2b)(-3a-2b)
=-(2a-3b)^2-(3a-2b)[-(3a+2b)]
=-4a^2+12ab-9b^2-[-(9a^2-4b^2)]
=-4a^2+12ab-9b^2+9a^2-4b^2
=5a^2-13b^2+12ab
= =
原式中(-2a+3b)=-(2a-3b);(-3a-2b)=-(3a+2b);
原式改写为-(2a-3b)(2a-3b)+(3a-2b)(3a+2b),化简后得
5a方-5b方。
=(2a-3b)(-1)(2a-3b)-(-1)(3a+2b)(3a-2b)
=(-1)(4a*a-12ab+9b*b)- (-1)(9a*a-4b*b)
=5a*a-13*b*+12ab
5(a*a*b-3*a*a*b)-2*(a*a*b-7*a*b*b)
(a+2b)(a-2b)+(a-b)(a+b)-2(a-3b)(a-b)
(2/3a)-[2/(a+b)]{[(a+b)/3a]-a-b}÷[(a-b)/b]
(2/3a)-[2/(a+b)]{[(a+b)/3a]-a-b}÷[(a-b)/a]
化简:[2/3a - 2/(a+b) * (a+b/3a - a - b)] / (a-b)/a
(2a-3b)[(a+b)-b(a-3b)]
a^2(a-b)+b^2(b-a) 因式分解 (a-b)^3-(a-b)^2 因式分解
2(a+3b)²-8(a+b)(a-b)-(a+3b)(a-b)
A-B A+B 2B+A 3A-B 6A+2B
化简a/b(a-b)-b/a(a-b)其中a=3 b=-2
2(a+b)-[4(a+b)-3(a+b)]一[5(a-b)+(a-b)]过程
((a+2b)+(2a+3b))*(a+b)/2
2a(a-3b)-b(3b-a)
(3a+b)*(a-2b)*(2a+b)
(3a+2b)*(2a+b)*(a+b)=
计算(a-b)(b-a)^3+[(a-b)^2]^2
a/a-b 3b/2a-2b 通分
2a(a-b)-3b(2a-b)咋做化简!!!